Seligman's Principles of Economics - Taussig, F. W. (Quarterly Journal of Economics, 1906)
Seligman's Principles of Economics Get access F. W. Taussig F. W. Taussig Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 20, Issue 4, August 1906, Pages 622–633, https://doi.org/10.2307/1882727 Published: 01 August 1906